Hybrid mediator panel: A legal pluralism framework for resolving medical disputes under the Indonesian health law - Repelita Witri; Melita Widyastuti; Nanang Zuli Purwanto; Marsudi Dedi Putra; Carolina Kuntardjo (Science Midwifery, 2026)
Background The transformation of medical-legal relationships from a paternalistic to a contractual model in Indonesia has triggered complex disputes that conventional, legalistic mechanisms often fail to resolve fairly. While Law No. 17 of 2023 mandates non-litigation resolution, the current mediation framework remains trapped in a state-centric paradigm that marginalizes professional ethics and social norms. Research Gap A critical research gap exists in the prevailing legal monism approach, which creates a "justice gap" by failing to synchronize the disciplinary reviews of Article 308 with criminal judicial processes, thereby leaving healthcare workers vulnerable to criminalization and patients without substantive restoration. Method This study employs a normative-prescriptive research method with a qualitative-synthetic conceptual development design to reconstruct the mediation function. Findings The findings introduce a "Hybrid Mediator Panel" and a "Multi-Layered Screening" mechanism as a functional reconfiguration of Article 310 of Law No. 17 of 2023. This model integrates state law, professional ethics (deontological), and living law (deliberation) into a single convergent system to ensure that settlement agreements are not only legally enforceable but also sociologically valid. Contribution This study provides a strategic blueprint for the Indonesian government to implement restorative justice in health law, ensuring legal certainty for medical professionals while simultaneously achieving holistic justice and therapeutic recovery for patients.